Exploring the Infringing Behaviours of Students inside a University Classroom: - Rakhshinda Jabeen; Shaista Hassan Chashoo; Dr.Najmus Sarifa (STAI Miftahul Ula Nganjuk, 2020)
The infringing behaviour of students is defined as a set of undesired and objectionable behaviour that hampers the flow of teaching-learning activities inside the classroom. The student's problematic behaviour is something related to the student's disposition and temperament. This research intends to investigate how university teachers perceive student’s misbehaviour and throws light on the underlying causes behind these undesired behavioural traits. This research is based on a descriptive survey. In this research, 50 teachers teaching undergraduate students in various departments of King Khalid University have participated. The authors have collected the data manually by filling two sets of a questionnaire. The result of the study shows: what are some common inappropriate behaviour that a teacher encounters, and why a student displays various types of misbehaviours? The findings of this study will help to develop the establishment of a well-managed classroom.